Surgical abortion service reorganization in response to the COVID-19 pandemic: a unique experience of attending second trimester D&E procedures under spinal anesthesia as emergency procedures - Sium, Abraham Fessehaye; Grentzer, Jaclyn M.; Lucero-Prisno III, Don Eliseo; Prager, Sarah (Frontiers in Reproductive Health, 2024)
BackgroundThe COVID-19 pandemic created a massive shift in how health care systems interact with COVID testing for patients. To avoid delay in accessing second trimester surgical abortion at our hospital (St. Paul's Hospital Millennium Medical College) during this pandemic, dilation and evacuation (D&E) procedures were attended as emergency cases, instead of as elective surgical procedures, which then required adherence to the universal preoperative COVID-19 testing protocol. This study aimed at documenting the experience of this unique abortion service adjustment in response to the COVID-19 pandemic.MethodsThis was a retrospective descriptive study conducted at St. Paul's Hospital Millennium Medical College (SPHMMC) in Addis Ababa, Ethiopia, from April 1, 2021 to July 31, 2021. We reviewed second trimester surgical abortion cases managed with D& E procedures, performed under spinal anesthesia using the emergency COVID-19 pre-operative testing protocol. Data were analyzed using SPSS version 23 and simple descriptive statistics were applied. Percentages and proportions were used to present the results.ResultsNineteen cases of second trimester D&E cases were reviewed. The median gestational age of the abortion clients was 21.57 weeks. Eight of 19 cases had cervical preparation with overnight intra-cervical Foley catheter placement while the rest 11 (57.9%) cases had their cervical preparation with Laminaria. The median time interval from initial evaluation of the abortion client to time of doing D& E procedure was 21.83 h.ConclusionSurgical abortion service reorganization enabled abortion clients to access dilation and evacuation procedures within 24 h of their initial presentation. This prevented significant delays in accessing abortion care that could otherwise have occurred as a result of adhering to the preoperative COVID-19 testing protocols applied to elective surgeries.